Бизнес-процесс создания уникального санаторно-курортного и туристического продукта для индивидуального потребителя - Круликовский, А.П.; Маланин, А.Е. (Культура народов Причерноморья, 2013)
В статье предлагается методология интерактивного создания санаторно-курортного и
туристического продукта. Реализация процессов самообслуживания при создании туристического
продукта, использование сети Интернет позволяет наиболее полно удовлетворять требованиям
разнообразных потребителей в различные курортные сезоны, что позволит уменьшить сезонность
санаторно-курортного и туристического бизнеса. У статті пропонується методологія інтерактивного створення санаторно-курортного й
туристичного продукту. Реалізація процесів самообслуговування при створенні туристичного
продукту, використання мережі Інтернет дозволяє найбільше повно задовольняти вимогам
різноманітних споживачів у різні курортні сезони, що дозволить зменшити сезонність санаторно-
курортного й туристичного бізнесу. The role of the health resort and tourist complex in the modern economy of Ukraine is great. The
development of the complex has an impact on many sectors of the economy: transport and communications,
agriculture and construction, among others.
Health resort business and tourism subject to sharp seasonal fluctuations, which may pose significant difficulties
in enterprise activity.Increase the efficiency of enterprises sanatorium-resort and tourist complex is possible with the help attract to rest
and recuperation individuals. For this it is necessary to provide customers with a variety of information about
our services, to create new, individually-oriented tourism products in real time.
To increase the efficiency of operations and improve the competitiveness of sanatorium-resort complex and
tourism need to use a variety of information technology. Analysis of studies of new information technologies has
shown that their use can improve the tourism product sales, lead to a uniform distribution of load and
enterprises spa complex, and improve customer service.
Tourism product is a comprehensive cross-sectoral in nature and includes a variety of resources in the region:
natural, social-economic and cultural objects and their components. For different times of the year improving
tourism industry needs to offer various health resort and tourist product, which includes advanced capabilities
of all regional recreation.
In this paper, we propose a system for generating tourism product by interactive self-service customer in real
time. The company provides the customer with a wide range of services, the consumer himself selects interest
him in some order of preference, then prepared application is processed enterprise information system , and
failure to comply with the consumer, there are seasonal and other constraints , a request is sent to the consumer
, offering revise its product . The result is a completely new product for each individual customer that the
customer is actually himself and posing.
The introduction of self-service systems to create health resort and tourist product leads to transforming the
tourist area with a service organized tourists on a diversified scope of sanatorium and tourism oriented to meet
the diverse needs of individual travelers.